Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Penambahan Sumber Karbon Gula Lontar Cair terhadap Kandungan Selulosa, Lignin, Asam Pitat, Kadar Nitrit dan Saponin - Lie, Cinta Kristin; Mullik, Marthen L.; Dami Dato, Twen O.; Oematan, Gustaf (Yayasan Sumber Daya Manusia Cerdas, 2024)
The purpose of this study was to determine the effect of the addition of liquid palm sugar as a carbon source in the Chromolaena odorata biofermentation process on cellulose, lignin, phytic acid, nitrite and saponin content. This study used a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments were: LB0 = 0 days of biofermentation, LB7 = 7 days of biofermentation, LB14 = 14 days of biofermentation, and LB21 = 21 days of biofermentation. The variables observed were cellulose, lignin, phytic acid, nitrite and saponin content. The data obtained were analyzed using Analysis of Variance and Duncan's test. The results showed that the length of biofermentation time significantly decreased cellulose content with a range of (23.52-19.26%), lignin (13.75-8.72%), phytic acid (4.03-2.00%), nitrite content (6.60-4.73ppm), and saponin (7.68-5.84%). It was concluded that the length of Chromolaena odorata biofermentation time decreased the content of cellulose, lignin, phytic acid, nitrite content and saponins with varying lengths of biofermentation time, namely the length of biofermentation time of 7 days (LB7) getting a total value of cellulose content (20, 40%), lignin (9.23%), the length of biofermentation time of 14 days get the total value of phytic acid content (2.23%), nitrite (4.86ppm) and the length of biofermentation time of 21 days get the total value of saponin content (5.84%).